East Asian FTAs in Services - World Bank (Washington, DC, 2014)
Bilateral and regional free trade agreements (FTAs) are proliferating across the globe, fundamentally altering the governance of world trade. Many of the recently concluded FTAs are comprehensive in their coverage, seeking to not only dismantle barriers to trade in goods but also the liberalization of trade in services. What have FTAs in services actually accomplished? This paper offers an assessment of the new generation of services agreements that have been concluded in the East Asia region. Until recently, governments in this region had been hesitant to enter into bilateral or regional arrangements. Yet since the year 2000-when only one regional services agreement was in force-twenty-four agreements have been signed that include at least one party in East Asia. Additionally, around 40 FTAs are currently being negotiated in the region, which suggests an even more prominent role for FTAs in the future.